The Effectiveness of Didactic Teaching Methods in Maternal and Newborn Nursing and Midwifery I - บูรณธนิต, ชุุติมา; วิทยโชคกิติคุณ, นิรนาท; เอกลัคนารัตน์, ศรีสุดา; วิบูลย์วัฒนกิจ, รพีพรรณ (Ganesha Journal, 2019)
This descriptive study was to examine the effectiveness of didactic teaching methods among nursing students in Maternal and Newborn Nursing and Midwifery I at Boromarajonani College of Nursing, Sawanpracharak, Nakhonsawan. The population consisted of 165 third year nursing students, academic year 2017. The instruments composed of the course specification, lesson plans, learning achievement evaluation and the satisfaction questionnaire related to learning and teaching methods. Data analyzed utilizing frequency, percentage, mean, standard. The results showed that learning achievement of nursing students was at a good level and the satisfaction of didactic teaching method was at a high level in overall parts, including instructor, teaching method, learning climate, and students. Recommendations: College should provide learning facilities and create atmosphere in order to make the teaching and learning process run efficiently and help to enhance learning progress as well as strengthen student’s discipline.